Long Non-coding RNA TUG1 Modulates Expression of Elastin to Relieve Bronchopulmonary Dysplasia via Sponging miR-29a-3p - Zhong, Qinghua; Wang, Li; Qi, Zhiye; Cao, Jia; Liang, Kun; Zhang, Caiying; Duan, Jiang (Frontiers in Pediatrics, 2020)
Objective: Multiple studies have highlighted that long non-coding RNAs (lncRNAs) may exert paramount roles in relieving bronchopulmonary dysplasia (BPD). The aim of our investigation is to probe the role and mechanism of lncRNA taurine up-regulated gene 1 (TUG1) in BPD. Methods: The current mouse model of BPD was simulated by induction of hyperoxia, and hyperoxia-induced MLE-12 cells were established as cellular model. Quantitative real-time polymerase chain reaction (qRT-PCR) was applied to determine relative expressions of TUG1, miR-29a-3p and elastin (ELN). We assessed cell apoptosis by TdT-mediated dUTP-biotin nick end-labeling (TUNEL) staining. Western blot was used for detection of apoptosis-related proteins. Moreover, cell viability was tested by cell counting kit-8 (CCK-8) assay. Inflammatory factors were measured by enzyme-linked immunosorbent assay (ELISA). Dual luciferase reporter (DLR) assay was employed to confirm relationship between genes. Results: Up-regulation of miR-29a-3p was found in lung tissues of BPD mice compared with lung tissues without BPD, while down-regulations of TUG1 and ELN were discovered in BPD tissues in comparison with tissues without BPD. Increasing TUG1 was shown to alleviate lung injury of BPD mice and promote proliferation of hyperoxia-induced MLE-12 cells. Meanwhile, TUG1 inhibited inflammatory response and cell apoptosis in lung tissues of BPD mice and hyperoxia-induced MLE-12 cells. MiR-29a-3p was targeted by TUG1 and negatively modulated by TUG1. ELN was inversely regulated by miR-29a-3p. Meantime, suppressive effects of TUG1 on apoptosis and inflammation were reversed by decreasing ELN or increasing miR-29a-3p in hyperoxia-induced MLE-12 cells. Conclusion: LncRNA TUG1 relieved BPD through regulating miR-29a-3p/ELN axis, which provided a therapeutic option to prevent or ameliorate BPD.